THE EFFECT OF SOCIAL MEDIA MARKETING ACTIVITIES ON BRAND LOYALTY WITH BRAND IMAGE AND BRAND AWARENESS AS MEDIATION VARIABLES AT XYZ BEAUTY CLINIC IN JAKARTA - Sukidy, Beatrice; Achmadi, Hendra (The International Journal of Medical Science and Health Research, 2024)
Background: Social media has become an effective platform for marketing products and increasing brand existence amidst intense business competition. Methods: This research aims to examine the influence of social media marketing activities on brand awareness, brand image and brand loyalty in the beauty clinic industry. These concepts were measured as mediating variables, and research was conducted on 160 respondents who were customers of beauty clinics using quantitative methods and SEM-PLS analysis. Result: Social media marketing activities have a positive influence on brand awareness, brand image and brand loyalty. Brand awareness has a positive effect on brand image, which in turn has a positive effect on brand loyalty. Apart from that, brand awareness also has a direct positive influence on brand loyalty. Conclusion: These findings support previous literature which shows that social media plays an important role in shaping consumer perceptions of brands and building consumer loyalty.